Cherednik algebra for the normalizer - Fallet, Henry (Comptes Rendus. Mathématique, 2022)
Ginzburg, Guay, Opdam and Rouquier established an equivalence of categories between a quotient category of the category $\mathcal{O}$ for the rational Cherednik algebra and the category of finite dimension modules of the Hecke algebra of a complex reflection group $W$. We announce a generalization of this result to the extension of the Hecke algebra associated to the normalizer of a reflection subgroup.